Husbands' Participation in Housework and Child Care in India. Issue 3 (June 2014) - Luke, Nancy; Xu, Hongwei; Thampi, Binitha V.
<x xml:space="preserve">Abstract</x> The authors tested theories of housework among tea plantation workers in India, where women comprise the main part of the workforce and are breadwinners in their families. Analysis of 49 semistructured interviews and survey data from 3, 181 female workers revealed that although women were mainly responsible for domestic labor, more than half of husbands usually or sometimes helped their wives with cooking, fuel wood collection, and child care. The analyses revealed a curvilinear relationship between husbands' earnings share and their participation in each task, supporting theories of bargaining and gender display. The probability of male participation decreased to its lowest level when men earned less than their wives. Husbands rarely helped with clothes washing—considered the most feminine task—and their participation did not respond to changes in relative earnings. These results support the authors' argument that patterns of bargaining and gender display will vary depending on the gendered nature of housework tasks within a particular society.